2016
DOI: 10.1080/09273948.2016.1178303
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Conjunctivitis and the Associated Risk of Migraine Among Children: A Nationwide Population-based Cohort Study

Abstract: Children with AC had a higher incidence and subsequent risk of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This study has several limitations. Although we adjusted for several potential confounders in the statistical analysis, several possible confounding variables associated with migraine, including family history of migraine, dietary habits, physical activity, occupational exposures, family member's smoking habits, stress, and emotional factors, were not included in our database 34 35. Besides, detailed information and laboratory data related to allergy, including serum IgE levels, eosinophil levels, skin prick tests, and family histories of atopy, were also unavailable in the database.…”
Section: Discussionmentioning
confidence: 99%
“…This study has several limitations. Although we adjusted for several potential confounders in the statistical analysis, several possible confounding variables associated with migraine, including family history of migraine, dietary habits, physical activity, occupational exposures, family member's smoking habits, stress, and emotional factors, were not included in our database 34 35. Besides, detailed information and laboratory data related to allergy, including serum IgE levels, eosinophil levels, skin prick tests, and family histories of atopy, were also unavailable in the database.…”
Section: Discussionmentioning
confidence: 99%
“… 11 12 26 Recently, population-based studies have been performed to overcome these limitations whereas most of them have still targeted children and adolescents or have examined the correlation between migraine and atopic disorders other than AD. 15 27 Previous studies have evaluated the risk of migraine in children with atopic disorders, and the increased risk of migraines has been explained by several stimuli in the brain development process caused by allergic diseases. 27 However, in this study, we analyzed the risk of migraine in patients older than 20 years to determine the effect of atopic disorders on the risk of migraine in adults.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Previous epidemiological studies in children suggested that atopic disorders at a pediatric age can affect brain development and increase the risk of migraine. 15 27 A population-based study in Taiwan found higher association of migraine and AR (adjusted odds ratio [aOR], 2.17; 95% CI, 2.09–2.26), asthma (aOR, 1.76; 95% CI, 1.66–1.87), and AD (aOR, 1.74; 95% CI, 1.58–1.93) compared to controls in children aged 7 to 18 years. 27 According to a previous study, boys showed greater risk of migraine than girls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 It has been associated with several immunemediated conditions including asthma, allergic rhinitis, allergic conjunctivitis, atopic disease, coeliac disease, inflammatory bowel diseases, systemic lupus erythematosus and Sjögren's syndrome. [16][17][18][19] The possible role of mode of delivery has not been examined in prior studies of migraine. We hypothesised that caesarean section increases the risk of migraine and our aim was to explore the association between being delivered by caesarean section and migraine later in life.…”
Section: Introductionmentioning
confidence: 99%